2005
DOI: 10.1073/pnas.0501190102
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy promotes MHC class II presentation of peptides from intracellular source proteins

Abstract: MHC-peptide complexes mediate key functions in adaptive immunity. In a classical view, MHC-I molecules present peptides from intracellular source proteins, whereas MHC-II molecules present antigenic peptides from exogenous and membrane proteins. Nevertheless, substantial crosstalk between these two pathways has been observed. We investigated the influence of autophagy on the MHC-II ligandome and demonstrated that peptide presentation is altered considerably upon induction of autophagy. The presentation of pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
522
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(542 citation statements)
references
References 44 publications
16
522
0
4
Order By: Relevance
“…Interestingly, composite exposure to TNF‐ α and IFN γ leads to significant autophagy‐dependent translocation of intracellular MHC class II to the cell surface in myocytes and more than 40% of muscle fibers in IBM that costain for autophagosomes and MHC class II have contact to CD4 + and CD8 + infiltrating T cells 108. Dengjel and colleagues reported that upregulation of autophagic activity, by means of altered lysosomal processing, significantly increases the fraction of intracellular source protein‐derived peptides presented on MHC class II 267. These findings suggest that the proinflammatory environment in IBM muscle promotes induction of autophagy in myofibers and subsequently enhances surface MHC class II, thereby maintaining CD4 + T cell infiltrates via the presentation of yet unknown self‐peptides.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 99%
“…Interestingly, composite exposure to TNF‐ α and IFN γ leads to significant autophagy‐dependent translocation of intracellular MHC class II to the cell surface in myocytes and more than 40% of muscle fibers in IBM that costain for autophagosomes and MHC class II have contact to CD4 + and CD8 + infiltrating T cells 108. Dengjel and colleagues reported that upregulation of autophagic activity, by means of altered lysosomal processing, significantly increases the fraction of intracellular source protein‐derived peptides presented on MHC class II 267. These findings suggest that the proinflammatory environment in IBM muscle promotes induction of autophagy in myofibers and subsequently enhances surface MHC class II, thereby maintaining CD4 + T cell infiltrates via the presentation of yet unknown self‐peptides.…”
Section: Degenerative Pathomechanisms In Ibmmentioning
confidence: 99%
“…However, it can be speculated that pGE may function to generate an array of tissue-restricted proteins that can subsequently be processed into peptides by autophagic proteases for presentation on MHC molecules (Dengjel et al 2005). Similar to the presentation of tumour-associated antigens (Reuschenbach et al 2009), senescent cells may also present antigens that can be recognized by immune cells, thereby becoming antigen-presenting cells (APCs).…”
Section: The Senescent Phenotype and Promiscuous Gene Expressionmentioning
confidence: 99%
“…Il est en revanche probable qu'elle contribue à l'activation des LB dépendant des LT au cours de la présentation antigénique. L'autophagie favorise en effet la présentation d'antigènes cytosoliques du soi [32] ou d'antigènes viraux intracellulaires par le CMH-II [33]. Si aucune étude n'a montré la pertinence de ces observations in vivo, il apparaît néanmoins possible que l'autophagie, par la présentation antigénique aux LT CD4 + spécifiques d'antigènes intracellulaires, contribue à l'activation de LB autoréactifs ou spéci-fiques d'antigènes viraux.…”
Section: Le Rôle De L'autophagie Dans La Survie Et L'activation Des Lunclassified